A combination therapy of nanoethosomal piroxicam formulation along with iontophoresis as an anti‐inflammatory transdermal delivery system for wound healing. Issue 5 (8th August 2019) - Kazemi, Mostafa; Mombeiny, Reza; Tavakol, Shima; Keyhanvar, Peyman; Mousavizadeh, Kazem
Abstract: Inflammation accounts as one of the major phases in wound healing, while prolonged and chronic inflammation may lead to adverse pathological conditions. Therefore, transdermal delivery of nonsteroidal anti‐inflammatory (NSAIDs) such as encapsulated piroxicam into a nanocarrier seems to be promising. For the first time, a nanoethosomal piroxicam of <200 nm was prepared and combined with iontophoresis. Results showed that there was a critical point at the concentration of 5 mg lecithin with the smallest particle size. Besides, lecithin concentration had direct and inverse linear relationships with turbidity and pH of nanocarriers, respectively. Moreover, as there was no linear relationship between the lecithin concentration and particle size, the effect of lecithin concentration was dominant on turbidity compared with particle size. It seems that a pH higher than 5.5 disturbed the linear relationship of pH and entrapment efficacy percentage (EE%) while at the pH range of 4 to 5.5, the relationship was linear and EE% gradually decreased with increasing pH. These data showed that an optimised nanocarrier with special physicochemical properties is dominant to the just particle size. Besides, ex vivo permeation studies in rat skin showed that there was no significant difference between the permeation of free drug and ethosomal ones. However, iontophoresis significantly enhanced ethosomal piroxicam permeation compared with the free drug. Overall, these data emphasise the superiority of iontophoresis for the transdermal delivery of nanoethosomal medications while nanoethosomal delivery without iontophoresis did not show significant transdermal potential. To sum up, transdermal nanoethosomal piroxicam along with iontophoresis seems to be promising in wound healing.